Czy nauczanie o Kościele zawarte w Listach św. Hieronima wpisuje się w postulaty Soboru Watykańskiego II? - Łukaszczyk, Michał (Vox Patrum, 2024)
The Second Vatican Council formulated its ecclesiological teaching on the basis of the concept of communio. It involved turning to the Bible, the teaching of the Church Fathers and the liturgy. This choice resulted in a move away from the juridical language inherent in pre-secular ecclesiology to a religious language that drew concepts from the Bible and the teaching of the Church Fathers, thus emphasising their theological teaching. One of the extremely important Church Fathers writing in the golden age of theology was Jerome of Stridon. The teaching on the Church contained in his Epistles should be considered from two aspects. First, the monk from Bethlehem is particularly sensitive to the emerging heresies, which he condemns extremely strongly, drawing attention to the threats to the unity of the Church. In the article, the heresy of Pelagianism is presented as an example. The second particularly valuable aspect of Jerome’s ecclesiology is his teaching on the Church based on the proper interpretation of Scripture. Exegesis is the main source of teaching about the Church. This teaching is deeply connected to Christ and to personal experience of faith. Stridonian gives his ecclesiology a Christological meaning, which bears the hallmarks of an eschatological Christology. An ecclesiology understood in this way, based on a correct interpretation of Scripture and pastoral care manifested in warning against the pernicious influence of heresy, is in line with the teaching of Vatican II.